+0  
 
+1
48
3
avatar+37 

Find all values of $t$ such that $6^{3t-1} =36^{t-3}$.

 

coolcoolcoolcoolcoolcoolcoolcoolcoolcoolcoolcoolcoolcoolcoolcoolcoolcoolcool

 Sep 14, 2020
 #1
avatar
+1

The only "real" solutions is when t = - 5

 

6^-16 = 36^ - 8

6^-16 = (6^2)^-8

6^-16 = 6^-16

 

There is also a "complex" solution when t = -5 * [(2.i.pi.n) /ln(6)]

 Sep 14, 2020
 #2
avatar
+1

63t - 1  = 36t-3

63t - 1  = 62(t-3)

3t - 1 = 2t - 6

t = -5

 Sep 14, 2020
 #3
avatar+37 
+1

Thanks cool

 Sep 14, 2020

54 Online Users

avatar